Lithium Nephrotoxicity: When Is the Time for Nephrology Con¬sultation? - Shokoufeh SAVAJ; Maryam FARASATINASAB; Atefeh AMOUZEGAR; Maryam RAHIMI; Mohammad HOSSEINZADEH (Tehran University of Medical Sciences, 2016)
No Abstract.